Attracting FDI in middle-skilled supply chains - Theodore Moran; Holger Görg; Adnan Serič; Christiane Krieger-Boden (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
While popular opinion often pictures FDI flowing in search of lowest-wage, lowest-skilled activities in emerging markets, actual FDI to such countries increasingly addresses medium to high-skilled manufacturing sectors. Such FDI might be called 'Quality FDI' that contributes to the creation of decent and value-adding jobs, enhancing the skill base of host economies, facilitating transfer of technology, knowledge and know-how, boosting competitiveness of domestic firms and enabling their access to world-wide markets, as well as operating in a socially and environmentally responsible manner. To attract such quality FDI, host countries need mindfully tailored policies. Recent research offers evidence for strategies in developing countries that successfully turned FDI into such quality FDI.
Keywords: F14; F16; O24; O25; 330; Foreign direct investment; developing countries; emerging countries; industrial policy